The relation of bacteria to the home - Briggs, Martha Amelia (My University, 1902)
Introduction: Until recently, a knowledge of bacteria, was considered essential only to physicians, or such persons wishing to make a special study along that line, but that time is passed and today every man and woman is expected to have a general knowledge of the subject of bacteriology and its relation to the home. Bacteria may be defined as single celled plants, microscopic in size, usually destitute of chlorophyll and reproducing by fission. By microscopic examination it has been found that bacteria are composed of a cell wall and cell contents. The cell contents is composed of protoplasm, as is also the cell wall, in the latter case however we find the protoplasm in a more condensed form. The contents of some bacteria contain starch grains while others do not. Whether bacteria contain a nucleus or not is a question as yet unsettled. We find in the study of bacteria that various conditions are favorable to their growth while other conditions are not favorable. The conditions that affect bacteria are moisture, temperature, light, electricity, chemicals, movement and the presence of other bacteria.
Citation: Briggs, Martha Amelia. The relation of bacteria to the home. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Bacteria; Cleanliness; Home Economics; Theses; Manuscripts (documents)